2022
DOI: 10.1109/jstars.2022.3176612
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Image Interpretation With Semantic Graph-Based Methods: A Survey

Abstract: With the significant improvements in Earth observation (EO) technologies, remote sensing (RS) data exhibit the typical characteristics of Big Data. Propelled by the powerful feature extraction capabilities of intelligent algorithms, remote sensing image interpretation has drawn remarkable attention and achieved progress. However, the semantic relationship and domain knowledge hidden in massive RS images have not been fully exploited. To the best of our knowledge, a comprehensive review of recent achievements r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…This necessitates the deblurring method to possess the capability to handle images with different scales. Finally, compared to natural images, remote sensing images usually contain similar regions within a scene with high correlation between pixels, 32 e.g., continuous trees in the forest and neatly arranged aircraft at the airport. Therefore, how to use the correlation between pixels to assist image restoration is important.…”
Section: Related Workmentioning
confidence: 99%
“…This necessitates the deblurring method to possess the capability to handle images with different scales. Finally, compared to natural images, remote sensing images usually contain similar regions within a scene with high correlation between pixels, 32 e.g., continuous trees in the forest and neatly arranged aircraft at the airport. Therefore, how to use the correlation between pixels to assist image restoration is important.…”
Section: Related Workmentioning
confidence: 99%
“…The interpretation of remote sensing imagery is a visual problem-solving activity which explores the relationship between objects present in the image to obtain the recognition of the image content. It is first based on the knowledge and experience of the analyst [34][35][36]. In geosciences, like aerial photo-interpretation, visual analysis of satellite imagery relies on several qualitative features of Earth's surface image, that are tone, texture, pattern, shape, context, and scale [37,38].…”
Section: Multi-temporal (Geographic Object-based) Analysismentioning
confidence: 99%
“…For example, Li et al (2021) [18] constructed a new remote sensing knowledge graph from scratch to support the inference recognition of unseen remote sensing images. In [22], the authors demonstrated the promising capability of remote sensing semantic reasoning in the intelligent remote sensing image interpretation field by constructing a semantic knowledge graph. However, as a relational database, both the data query (query matching using similarity of attributes of image objects) and knowledge inference capabilities of the knowledge graph are advantages worth investigating in remote sensing image interpretation.…”
Section: Introductionmentioning
confidence: 99%